Gastroprotective effect of Canna edulis Ker. ethanolic extract in piroxicam-induced rats - Dara Pranidya Tilarso; Moch. Saiful Bachri; Wahyu Widyaningsih (Universitas Ahmad Dahlan, 2021)
Medications derived from plants and pure natural ingredients have far lower side effects and risks than synthetic drugs. One side effect of piroxicam is irritation of the digestive tract. One of the therapeutic preventions to minimize peptic ulcers was utilizing Canna edulis Ker. This study aims to prove that ethanolic extract of Canna edulis Ker. can be used as an alternative to prevent piroxicam-induced peptic ulcers based on ulcer index parameters and the protection ratio. The rats were divided randomly into 6 groups consisting of 5 rats. The normal group was given food and water. The negative control group was given 0.5% CMC-Na. The extract groups were given various doses of ethanolic extract of Canna edulis Ker. (50, 100, and 200 mg/kg BW). The positive control was given sucralfate at 360 mg/kg BW dose. Rats were treated orally for 14 days. One hour after the treatment on the 14th day, all groups except group I were orally administered with piroxicam dissolved in 0.5% CMC-Na at 1.8 mg/kg BW dose. Twenty-four hours later, animals were sacrificed, dissected, and their stomach organs were removed to analyze its number of ulcers. Ulcer observation was formed by giving a score and protection ratio. The mean ulcer index value was 0.33±0.58 for 50 mg/kg BW and 100 mg/kg BW ethanol extract treatment groups, while the 200 mg/kg BW group showed 0.67±0.58. The protection ratio was 83.33±28.87 in 50 mg/kg BW and 100 mg/kg BW treatment groups, while 66.67±28.87 was shown in the 200mg/kg BW group. Canna edulis Ker. ethanolic extract has the gastroprotective ability by decreasing the index of gastric ulcers and increasing the protection ratio to the stomach of piroxicam-induced rats.